DIPLOMASI GEISHA JEPANG DAN DAMPAKNYA PADA PERSEPSI ANGGOTA-ANGGOTA LVRI (LEGIUN VETERAN REPUBLIK INDONESIA) KOTA MALANG TERHADAP JEPANG - M. Syaprin Zahidi (Jurusan Ilmu Hubungan Internasional, 2019)
Japanese Geisha Diplomacy is an important effort of the Japanese government in changing the international community's perception of Japan in treating women. This article seeks to analyze the Geisha Diplomacy in the context of the impact it has on the perceptions of members of the Republic of Indonesia Veterans Legion (LVRI) towards Japan. The analysis in this paper uses the concepts of cultural diplomacy, women's diplomacy and perception theory. Analysis of the perceptions of members of the Republic of Indonesia Veterans Legion (LVRI) shows that their perception of Japan is increasingly positive, especially after the emergence of Geisha Diplomacy by Japan.